Understanding the Benefits of Regional Integration to Trade : The Application of a Gravity Model to the Case of Central America - Gordillo, Darwin Marcelo (2012)
The paper identifies the impact of physical barriers to trade within Central America through the use of an augmented and partially constrained Gravity Model of Trade. Adjusting the Euclidian distance factor for Central America by real average transport times, the model quantifies the impact of poor connectivity and border frictions on the region's internal trade as well as its trade with external partners, such as the United States and Europe. In addition, the authors benchmark Central America's trade coefficients against those of a physically integrated region by running a parallel Gravity Model for the 15 core countries of the European Union. This allows for the estimation of potential intra-regional and external trade levels if Central America were to reduce border frictions and time of travel between countries and thus benefit from both the adjacency of each country's neighbors and the gravitational pull of the region's economies. The analysis is conducted for all of Central America's trade and is also disaggregated for three groups of products -- processed fruits and vegetables; steel and steel products; and grains -- by both volume and value. This differentiation tests the consistency of the results while providing insight into the differentiation in trading patterns and potential for these containerized, break-bulk, and bulk products. The results of the model include a potential doubling in intraregional exports if Central America could achieve the adjacency and time-distance factors of a truly integrated region. In addition, the region's combined exports to the European Union and the United States are projected to increase by more than a third compared with the current level, assuming European Union-level adjacency performance. Even more external trade benefits would accrue by reducing the economic penalty imposed by overland transport and border crossing inefficiencies.